Pemanfaatan Layanan Google Drive Untuk Menjalankan Aplikasi Pengontrolan Peralatan Listrik Menggunakan Usb Comm Port - Rommy Oktaviandi; Dahliyusmanto Dahliyusmanto; Anhar Anhar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The need for a system for remote controlling is increasing in line with the era of globalization in which migration and movement of people more widely and quickly. So far, the public can control something remotely by using the remote control. However, such control is hampered by distance, if the distance between the tool is controlled by the controller passes the tolerance limit, then the equipment can not function as desired. From the above, the authors use of internet technology to make long-distance control system. The method is performed by utilizing the cloud computing facilities at google drive. Using Visual Basic 2010 to build an interface that allows the user in controlling electrical equipment integrated in a USB Comm Port. Results from this study are electrical appliances can be controlled from a distance with minimum delay 12s.Keywords; Internet, Visual Basic, Google Drive, Usb Comm Port, Cloud Computing